Incentive scheme and productivity in microfinance institutions in Benin - SENOU, Melain Modeste; ACCLASSATO HOUENSOU, DENIS (My University, 2019)
This article aims to analyze the productive effects of financial and non-financial incentive in microfinance institutions in Benin. We estimate a Cobb-Douglas production function augmented by the Incentive Scheme on an unbalanced panel of 14 registered MFIs over the period 2007-2017. Findings of this study show that non-financial incentives positively impact the outreach whereas the financial incentives have a negative effect on outreach. They further suggest that a well-designed incentive scheme is a powerful tool to overcome free riding and other asymmetric information problems in a costly monitoring environment.
Keywords: Financial incentive; Non-Financial Incentive; Productivity; MFI; Benin